Pemikiran Hadis Kaum Modernis Indonesia : (Analisis Pemikiran Hadis Soekarno) - Muhammad Anshori (Prodi Ilmu Hadis Fakultas Ushuluddin dan Dakwah Universitas Islam Negeri Madura, 2024)
This paper analyzes Soekarnoâ€™s thoughts on hadith. Hadith studies that have developed so far are still Arab-oriented, rarely in the context of Indonesia. Using the descriptive-analytical method, this paper tries to explain Soekarno's hadith thoughts that are scattered in several of his books. Soekarno is known as a modernist thinker who is critical in reading religious discourses, including hadith. Among the themes of hadith studies raised by Soekarno in this paper are the importance of hadith studies, á¸aâ€™Ä«f hadith, and the methods of understanding hadith